Acionamentos biográficos no jornalismo em revista: uma análise das histórias de vida de Lula e Obama em Veja e Time - Michele da Silva Tavares (2016)
This research deals with how life stories are told by journalistic texts of newsmagazines. It is understood that the journalist who deals with the biographical elements in the report is not necessarily a biographer, but interchanges tensions and ways of "doing" the biographical. Despite not having the pretensions of the materialized narrative in the book, he has the intentions of the editorial line as a guide and the vectors of socio-political scenario and production context. The magazine, in its materiality, provides a reflection on the joints of the texts (titles, subtitles, news), images (photographs and several illustrations) colors and textures that adorn the events and reinforce the senses and symbologies about the world around. The central objective of this research is to provide subsidies to understand how the reports of Veja and Time rely biographical features of the characters Luis Inacio Lula da Silva and Barack Obama, during the coverage of the election year, for an appreciation of the individual on the journalistic text in its verbal and visual dimension. The cut scene for analysis, which motivates journalism to trigger the biography is the presidential election in Brazil in 2002, and the United States, in 2008. In general, it sought to elucidate the gestures of biographical journalism from the effects of meaning generated by what is actuated (relations of temporality, memories and imaginary). From a theoretical point of view, we discuss a notion of biography considering its conceptual crossings and tangentially with the perceptions of authors who deal with life stories from news stories, highlighting the dimension of ingenuity and imbued with delusion in the biographical reconstruction. Also feature the device "magazine", we reflect on the uniqueness of the electoral time associated with the notion of journalistic event and we draw some considerations on the public visibility of the presidential image. From a methodological point of view, we adopted semiotics, as a reading key and propose a way to read the printed text of magazines, from the verb-visual text perspective advocated by Gonzalo April (2007), which considers three dimensions of analysis : eye level, eye level and the level of the image. Structured in this triad, the analysis revealed that the existence of a biographical dimension seen in the journalistic text is linked to the setting in question and the events giving rise to the debate on the uniqueness of the life story of certain characters. In addition, textual gestures implemented by magazines revealed two uses of the biographic elements in the journalistic text: the need to know, understand and delve into the "new "(as featured with Obama) and intentional reinforcement previously known reading frames (as in the case of Lula).